Relationship Between Health Education on Breastfeeding Techniques and Burping Babies After Breastfeeding With Regusrgitation Incidents in Babies in Panyaungan Village in 2023 - Eha Putri Dewi; Mariyani Mariyani (International Journal of Health and Pharmaceutical (IJHP), 2024)
Background Regurgitation in infants is often caused by physiological reflux, which is a normal condition. The lower esophageal sphincter in infants is not fully mature, so food can go back up into the esophagus and out through the mouth. Purpose of Writing: for the relationship between health education on breastfeeding techniques and burping babies after breastfeeding with the incidence of regurgitation in babies in Panyaungan Village in 2023. Research Methods: The sample size in this study used a total side, namely 65 mothers who had babies aged 0-6 months in Panyaungan Village who were taken by total sampling. Collecting data to determine mother's knowledge about breastfeeding techniques and burping babies and the incidence of regurgitation was measured using a questionnaire. The data analysis used is the method of this research is an analytic survey with a case control design or retrospective study. Research Results In the chy-square test, the results obtained were P value 0.000 > 0.05, so the analysis was that there was a relationship between burping techniques and regurgitation events in Panyaungan Village in 2023. The OR calculation results were 5.556, which means that babies aged 0-6 months have more regurgitation events 5.556 times higher by not or rarely doing burping techniques compared to doing burping techniques (95% CI 3.075 -10.038. Conclusions and Suggestions: It is hoped that the results of this study can be used as a reference that in order to reduce regurgitation it is necessary to provide education on breastfeeding techniques until breastfeeding mothers understand proper and correct breastfeeding techniques.